ALOKASI BIAYA BERSAMA UNTUK PRODUK GABUNGAN PADA CV. LESTARI AMBON - Septina. L. Siahaya (Ekonis: Jurnal Ekonomi dan Bisnis, 2016)
Allocation of costs together with the charging of fees along to the object of indirect costs or joint coststo the cost biaya. Object imposition to this range of products required for the calculation of the cost ofinventories, profit determination and financial reporting. This study aims to allocate shared costs forthe combined product CV. Lestari which has resulted in a wide range of bakery products with flavorsvarying. This shared cost allocation in turn can help companies in menentukkan the cost per unit foreach bread. Joint cost allocation method used is the market price method, the method of the averagecost per unit, and the weighted average method. Based on the results of the discussion obtainedproduct cost per unit for each type of bread whose value is not much different, it all turned out to bethe method used to produce the production cost per unit is higher than its market price of Rp. 800,-except for bakery products rich with the weighted average method which resulted in cost per unit ofRp. 654,-.Keyword: Cost Together.